1996
DOI: 10.1002/(sici)1096-9861(19961202)376:1<1::aid-cne1>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the dopaminergic innervation of forebrain areas relevant to learning: A combined immunohistochemical/retrograde tracing study in the domestic chick

Abstract: The mediorostral neostriatum/hyperstriatum ventrale (MNH) and neostriatum dorsocaudale (Ndc) of the domestic chick are crucially involved in auditory filial imprinting, whereas the lobus parolfactorius (LPO) seems to be involved in the emotional modulation of behavior. Because there is evidence that MNH and Ndc are akin to higher association areas in mammals, the present study evaluates the dopaminergic and thalamic input to these areas, as well as to the avian caudate/putamen homologue LPO, by using retrograd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 108 publications
5
66
0
Order By: Relevance
“…This is the case for the nucleus tegmenti pedunculopontinus pars compacta, located in the diencephalic-mesencephalic tegmentum . This cell field contains a large population of dopaminergic neurons that send a massive dopaminergic innervation to the striatal part of the basal ganglia in birds (i.e., the regions that have been called lobus parolfactorius and paleostriatum augmentatum; Kitt and Brauth, 1986a,b;Bailhache and Balthazart, 1993;Reiner et al, 1994;Szekely et al, 1994;Karle et al, 1996;Metzger et al, 1996; Durstewitz et al, 1999) and therefore is accepted as homologous to the substantia nigra pars compacta of other vertebrates Smeets and Reiner, 1994;Medina and Reiner, 1995;Reiner et al, 1998a). The name applied to this region in Karten and Hodos (1967) and in many subsequent atlases and published papers, however, incorrectly suggests a homology with the pedunculopontine tegmental nucleus of mammals, located in rhombomere 1.…”
Section: Revised Avian Brain Nomenclaturementioning
confidence: 99%
“…This is the case for the nucleus tegmenti pedunculopontinus pars compacta, located in the diencephalic-mesencephalic tegmentum . This cell field contains a large population of dopaminergic neurons that send a massive dopaminergic innervation to the striatal part of the basal ganglia in birds (i.e., the regions that have been called lobus parolfactorius and paleostriatum augmentatum; Kitt and Brauth, 1986a,b;Bailhache and Balthazart, 1993;Reiner et al, 1994;Szekely et al, 1994;Karle et al, 1996;Metzger et al, 1996; Durstewitz et al, 1999) and therefore is accepted as homologous to the substantia nigra pars compacta of other vertebrates Smeets and Reiner, 1994;Medina and Reiner, 1995;Reiner et al, 1998a). The name applied to this region in Karten and Hodos (1967) and in many subsequent atlases and published papers, however, incorrectly suggests a homology with the pedunculopontine tegmental nucleus of mammals, located in rhombomere 1.…”
Section: Revised Avian Brain Nomenclaturementioning
confidence: 99%
“…Tract tracing studies have so far revealed inputs from a wide range of pallial structures (i.e., avian homologues of isocortex such as the arcopallium and nidopallium) [54], the subpallial thalamus [55], and neuromodulatory nuclei including the ventral tegmental area (VTA) and substantia nigra (SN) for dopaminergic afferents [56][57][58][59], and the raphe nuclei in the pons for serotonergic afferents [60].…”
Section: Afferent Connection To Mst/nacmentioning
confidence: 99%
“…These data demonstrated that endomorphin-1 impaired long-term memory through 1 -opioid and endomorphin-2 through 2 -opioid receptors. Freeman and Young (2000) demonstrated that passive avoidance learning in chicks disrupted by endomorphin-2 may involve cytosolic and mitochondrial protein synthesis within the lobus paraolfactorius, which constitutes a structure homologous to the caudate putamen in mammals (Veenman et al, 1995;Metzger et al, 1996;Durstewitz et al, 1999). Endomorphin-2 was shown to reverse the amnesic effects of anisomycin and blocked cytosolic protein inhibition in this structure.…”
Section: A Biological Effects Of Endomorphinsmentioning
confidence: 99%